Traces of Contact in the Lexicon Austronesian and Papuan Studies - Klamer, Marian; Moro, Francesca (Brill, 2023)
What can the languages spoken today tell us about the history of their speakers? This question is crucial in insular Southeast Asia and New Guinea, where thousands of languages are spoken, but written historical records and archaeological evidence is yet lacking in most regions. While the region has a long history of contact through trade, marriage exchanges, and cultural-political dominance, detailed linguistic studies of the effects of such contacts remain limited. This volume investigates how loanwords can prove past contact events, taking into consideration ten different regions located in the Philippines, Eastern Indonesia, Timor-Leste, and New Guinea. Each chapter studies borrowing across the borders of language families, and discusses implications for the social history of the speech communities.